HYDROPONICS APPARATUS - HASHIMOTO TATSUTOSHI (2016)
PROBLEM TO BE SOLVED: To provide a hydroponics apparatus which reduces a work place in a plant factory to increase a planting area, promotes uniform growth of plant, and improves work efficiency of operators and energy efficiency.SOLUTION: A hydroponics apparatus is constituted in that a flow is generated in a water channel by inputting aqueous solution from one side of a U-shaped water tank 1 and pumping the solution from the other side, and approximately cylindrical planting panels 3 in which seeds of plant to be cultivated are input rotate by receiving force of the flow in the water channel. By inputting seeded panels from a pouring side of the aqueous solution and cropping from a pumped side of the solution, a seeding work and a cropping work can be performed without making an operator move.SELECTED DRAWING: Figure 1 【課題】植物工場における作業場所を減少させて作付面積を増加させ、植物の均一な成長を促すと共に、作業者の作業効率とエネルギー効率を高める水耕栽培装置を提供する。【解決手段】Ｕの字の水槽１の一方から、水溶液を投入し、他方からくみ上げることで、水路に流れを生じさせ、その水路中に栽培する植物の種を入れた略円筒状の植栽パネル３が、その流れの力を受けて回転するように構成した。水溶液の投入側から種蒔きしたパネルを投入し、くみ上げた側から、収穫することで、移動しないで、種付け、収穫作業ができる。【選択図】図１